Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Regional Development and Proximity Relations 2014
DOI: 10.4337/9781781002896.00006
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: the role of proximity relations in regional and territorial development processes

Abstract: Proximity analyses have nowadays turned out to be a part of the toolbox of regional scientists, and this notion has recently become very popular in the field of politics, and private or public stakeholders. Proximity is an argument for selling food or financial products, as well as a good slogan for local networks or social devices or even for policymakers.In parallel, the notion of proximity has spread in the academic literature and is now commonly used by scholars in regional science, geography and spatial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 105 publications
(87 reference statements)
0
15
0
2
Order By: Relevance
“…Proximity gains importance in the spatial context (Torre & Wallet, 2014); it refers to the state, quality, sense, or fact of being near or next in space, time, or relationship. The concept of proximity goes beyond the traditional interpretation of geographical closeness.…”
Section: General Model Of Regional Developmentmentioning
confidence: 99%
“…Proximity gains importance in the spatial context (Torre & Wallet, 2014); it refers to the state, quality, sense, or fact of being near or next in space, time, or relationship. The concept of proximity goes beyond the traditional interpretation of geographical closeness.…”
Section: General Model Of Regional Developmentmentioning
confidence: 99%
“…Previous studies have shown that geographical proximity is a necessary but not sufficient prerequisite for innovative organisational relations (Broekel-Boschma [2012] researchers examined other factors that influence inter-organisational relations and the transfer of knowledge and innovation through these organisational channels (Benos-Karagiannis-Karkalakos [2015], Karlsson-Gråsjö [2014], Torre-Rallet [2005]). These soft, but difficult to measure factors, were defined as proximity dimensions that are associated with relational (Harun-Noor-Ramasamy [2019]) and/or virtual spaces (Torre-Wallet [2014]). The terminology used in describing physical spaces or spatial entities stays the same in the case of relational and virtual spaces (Ojala [2015], Drejer-Østergaard [2017]).…”
Section: The Changing Role Of Proximitymentioning
confidence: 99%
“…Social norms contribute to this organized proximity. This logic is not, however, limited to spoken forms of interaction (Torre and Wallet, ). This is close to the notion of social capital explained in Ostrom and Ahn ().…”
Section: An Analytical Approach Based On Geographical and Organized Pmentioning
confidence: 99%
“…These relations contribute to creating, via a system of interactions, effects which structure their local environment (Kirat and Lung, ; Boschma, ). Torre and Wallet () distinguish three main meanings: the administrative region, the geographical dimension of development, and the local extended network. For these authors, territory is a ‘social construction’ combining economic interactions between actors, which generates dynamic territorial processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation